2013
DOI: 10.1111/apa.12416
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardiifor prevention of necrotizing enterocolitis in preterm infants: a randomized, controlled study

Abstract: Although Saccharomyces boulardii supplementation at a dose of 250 mg/day was not effective at reducing the incidence of death or NEC in VLBW infants, it improved feeding tolerance and reduced the risk of clinical sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 32 publications
1
77
0
1
Order By: Relevance
“…Twenty-eight trials [19,20,21,22,23,24,25,26,28,29,30,31,32,33,34,35,37,38,39,40,41,42,43,44,45,46,47] reported on late-onset sepsis. The administration of probiotics reduced the rate of sepsis in the pooled effect by 12% (typical RR 0.88, 95% CI 0.80-0.97, p = 0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-eight trials [19,20,21,22,23,24,25,26,28,29,30,31,32,33,34,35,37,38,39,40,41,42,43,44,45,46,47] reported on late-onset sepsis. The administration of probiotics reduced the rate of sepsis in the pooled effect by 12% (typical RR 0.88, 95% CI 0.80-0.97, p = 0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The administration of Lactobacillus GG [23,34,35,36] and Bifidobacterium lactis [25,37,29] species alone significantly reduced the incidence of severe stage II-III NEC (RR 0.31, 95% CI 0.12-0.76, and RR 0.24, 95% CI 0.10-0.58, respectively). The pooled effect of the included trials that utilized L. reuteri [38,40], B. breve [22,39] and Saccharomyces boulardii alone [24,45,62] showed a lack of significant reduction of severe NEC stage II-III (RR 0.71, 95% CI 0.37-1.39, and RR 0.92, 95% CI 0.67-1.28; RR 0.82, 95% CI 0.44-1.50, respectively). Subgroup analysis identified that mixtures of 2 types and mixtures of more than 2 types of probiotics were most beneficial in reducing the risk of NEC (RR = 0.34; 95% CI 0.17-0.67, p = 0.002, and RR = 0.40; 95% CI 0.26-0.64, p < 0.0001, respectively; online suppl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 3 publications from the same study population by Demirel et al (53)(54)(55) that evaluated the effect of probiotic supplementation on different outcomes; hence, we have considered these 3 publications as a single study. The total sample size in the review was 5895 subjects with a median of 183 subjects (range: 31-1099 subjects).…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic supplementation was shown to reduce the duration of hospitalization (43,50,60,62), incidence of feed intolerance (37,46,50,55,60), and duration of indirect hyperbilirubinemia (53). The supplementation improved weight gain in the hospital (37,46) and growth velocity (48).…”
Section: Secondary Outcomesmentioning
confidence: 99%